(untitled) (Revista Cocar, 2018)
Este artigo é fruto das investigações realizadas nos Relatórios Presidenciais do Brasil na década de 1970. O objetivo é investigar as Políticas de Assistência e Proteção à infância no Brasil, na referida década, analisando, sobretudo, os programas, projetos, ações e iniciativas de cunho educativo, cultural e de proteção às crianças e as relações destas políticas com o contexto econômico, social e educacional das crianças. A metodologia utilizada foi a pesquisa documental e tem como problemática indagar que políticas de Assistência e Proteção à infância foram implantadas no Brasil na década de 1970 e como essas se materializaram. Os resultados apontaram que as Políticas eram eugenistas e higienistas, com ações votadas para a assistência à maternidade, vacinação, erradicação de doenças e mortalidade infantil. Palavras-chave: Políticas. Assistência e proteção. Infância. Assistance and protection of childhood policies in the 1970s: a study in the Brazil presidential reports Abstract This article is the result of investigations carried out in the Brazil Presidential Reports in the 1970s, The objective of investigating the Child Protection and Protection Policies in Brazil in this decade, analyzing, above all, programs, projects, actions and initiatives Educational, cultural and protection of children and the relations of these policies with the economic, social and educational context. The methodology used was the Documentary research and has as problematic to inquire that policies of Assistance and Protection to the childhood were implanted in Brazil in the decade of 1970 and how these materialized? The results indicated that the Policies were eugenics and hygienists, with actions voted to maternity care, vaccination, disease eradication and infant mortality. Keywords: Policies, Assistance and protection, Childhood.